The Role Of The Principal In Enhancing The Performance Of Teachers And Educational Staff At Sma Negeri 1 Bengkulu Selatan - Yusuarsono, Yusuarsono; Lorita, Evi; Kader, Bando Amin C; Sari, Rozi Anita (Journal of Research in Social Science and Humanities, 2022)
This study aims to examine the role of the principal in improving the performance of teachers and educational staff at SMA Negeri 1 Bengkulu Selatan. The research employed a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation involving six key informants, including the principal, administrative staff, teachers, school committee, and student representatives. The findings indicate that the principal exercised leadership through five performance improvement strategies as outlined by Schuler and Jackson, namely positive reinforcement, performance audits, performance standards, feedback mechanisms, and recognition of achievement. The principal's role extended beyond administrative functions to reflect a transformational leadership style that fostered a collaborative, disciplined, and quality-oriented work culture. Nonetheless, challenges such as low participation in training programs and weak discipline among some educators were identified. These findings highlight the need to strengthen internal coaching systems and promote more participatory governance strategies within the school.